BEBERAPA SIFAT FISIKA TANAH PADA LAHAN USAHATANI KARET DAN KELAPA SAWIT RAKYAT DI DAS BATANG PELEPAT - ,, Sunarti (Universitas Jambi, 2011)
ABSTRACTRubber and oil palm farming land at Batang Pelepat Watershed was cultivated by some type. The objectives of this research were know influence rubber and oil palm farming types and secondary forest on some physical properties of soil and defined farming type that the best to maintain soil physical properties. The research was conducted by survai method and data was analyzed statistically according to randomized block design. The result of research showed that rubber and oil palm farming types with mixed cropping system the same as secondary forest in relation to bulk density, porosity total, and pore distribution of soil.